Enhancement of Pancreatic Cancer Therapy Efficacy by Type-1 Matrix Metalloproteinase-Functionalized Nanoparticles for the Selective Delivery of Gemcitabine and Erlotinib - Yin N; Yu H; Zhang X; Lv X (Dove Medical Press, 2020)
Na Yin, Hui Yu, Xiaodi Zhang, Xiaodan Lv Department of Pharmacy, Jinan Infectious Diseases Hospital Affiliated to Shandong University, Jinan 250000, People’s Republic of ChinaCorrespondence: Xiaodan LvJinan Infectious Diseases Hospital, No. 22029 Jingshi Road, Jinan 250000, People’s Republic of ChinaEmail lvxdjidh@tom.comPurpose: Pancreatic cancer (PCa) is projected to become the second leading cause of cancer-related deaths by 2030. Gemcitabine (GEM) combined with erlotinib (ERL) have been approved by the FDA for locally advanced, unresectable or metastatic pancreatic cancer therapy since 2005. Type-1 matrix metalloproteinase (MT1-MMP) has been recognized as a critical mediator of several steps in PCa progression including activating TGF-β or releasing latent TGF-β from LTBP-1, resulting in increased collagen production and cleavage collagen.Methods: In the present research, GEM and ERL co-loaded nanoparticles (GEM/ERL NPs) were prepared. A non-substrate MT1-MMP binding peptide was decorated onto the GEM/ERL NPs surface.Results: M-M GEM/ERL NPs exhibited the highest uptake ability (67.65 ± 2.87%), longest half-life period, largest area under the curve, and the best tumor inhibition efficiency (69.81 ± 4.13%). The body weight, blood urine nitrogen (BUN), aspartate aminotransferase (AST), and alanine aminotransferase (ALT) of the system were steady when tested in mice model.Conclusion: In conclusion, M-M GEM/ERL NPs protected the drugs in the plasma, improved cellular uptake capacity, exhibited the most remarkable tumor cell inhibition ability, and showed the most efficient tumor growth inhibition capacity in vivo. M-M GEM/ERL NPs could be applied as an efficient and safe system for the synergistic combination chemotherapy of PCa.Keywords: pancreatic cancer, gemcitabine, erlotinib, type-1 matrix metalloproteinase, lipid nanoparticles